Intratumoral injection of anlotinib hydrogel enhances antitumor effects and reduces toxicity in mouse model of lung cancer - Qin Gao; Shan Tang; Han Chen; Hui Chen; XiaoJie Li; YiQing Jiang; ShaoZhi Fu; Sheng Lin (Taylor & Francis Group, 2020)
This study was conducted to determine the antitumor effects and ability of an anlotinib (AL) hydrogel (AL-HA-Tyr) to reduce toxicity in a mouse model of Lewis lung cancer (LLC). We constructed a drug carrier system for AL, verified its effectiveness and systemic safety, and provided a preliminary experimental foundation for clinical carrier transformation. AL-HA-Tyr was prepared by encapsulating AL with hyaluronic acid-tyramine (HA-Tyr) conjugates. Colony and tube formation assays showed that AL-HA-Tyr restrained the proliferation of human umbilical vein endothelial cells (HUVECs) and LLC cells, respectively, in vitro, and that AL exerted significant anti-angiogenesis and anti-tumor effects. The invasion and migration of HUVECs and LLC cells were efficiently suppressed by AL according to transwell assays. HUVEC and LLC cell-cycle and apoptosis analysis clarified the direct anti-tumor effects of AL-HA-Tyr. Mice engrafted with LLC cells in vivo were administered oral saline, oral AL, or an intratumoral injection of HA-Tyr or AL-HA-Tyr. The results showed that AL-HA-Tyr obviously reduced visceral toxicity and decreased Ki67 and VEGF-A expression in tumor cells compared with AL. Furthermore, AL-HA-Tyr significantly prolonged the survival of tumor-bearing mice. Overall, AL-HA-Tyr enhanced antitumor effects and reduced toxicity in the LLC model. It provided a foundation for the clinical transformation of drug carrier systems.